Caracterización del Sistema de Tenencia y Morfológica del Ovino Criollo Ecuatoriano en la Provincia de Tungurahua - Muso Gancino, Marco Antonio (2018)
Preserving biodiversity means maintaining the variety of species and genetic resources as well as the environment in which the different species coexist and are interrelated. The project was carried out with the objective of evaluating the land tenure system and morphological characterization into Ecuadorian Creole Ovines. The investigation was carried out in Pilahuin Canton, Rumipata Center Sector in Tungurahua Province located at 4067.7 masl, with low and almost constant temperatures throughout the year, and abundant and regular rainfalls. One hundred Creole Ovines (ninety-two females and eight males) were mainly evaluated in their main morphological characteristics where the Zoometric cane, measuring tape and a compass of drill bits were used. The calculation of the medians were carried out, the maximum value and minimum value. It obtained averages of head length with 15.18 cm, snout diameter 15.12 cm, distance between encounters of 11.76 cm, thoracic diameter with 64.13 cm, thoracic capacity 69.03 cm, croup width 13.11 cm, rump length 15.41 cm, bicoastal diameter 16.4 cm , elevation to the back 52.16 cm, height of the breastbone 32.73 cm, raised to the rump 51.15 cm, body length 48.3 cm, diameter of the cane with an average of 5.91 cm and with a hair length of 12.62 cm. Likewise, it was determined the faneroptic characterization to have a straight head, their ears are small and have a semi-erect orientation with pigmentation of dark mucous, hooves with two-colored pigmented, present a small pigmented udder that determines that in this production are without any horns. Regarding, the comparison between males and females is determined that there are significant differences for the variables snout diameter, bicoastal diameter, diameter of the cane and length of hair which have favorable values superior in males and for the rest of the variables do not present significant difference with a value of (p < 0.05)